Natural gas to methanol process flowsheet improvement via integration of ITM oxygen technology - Fankomo, Phumzile (My University, 2024)
Current industrial gas-to-liquids (GTL) processes suffer high energy penalties and associated carbon emissions caused by inefficient energy utilization and recovery. With the increasing demand for methanol and stricter regulations requiring reduced carbon intensity, there is a need to improve efficiencies of the existing process. This study analysed the existing large-scale natural gas to methanol flow sheet and investigated development of a new and improved flow sheet. In a conventional natural gas to methanol process, the air compressors in the cryogenic air separation unit (ASU) as well as the syngas compressor in the methanol synthesis unit are the most energy intensive and contribute significantly to the energy cost of large-scale syngas manufacture. The conventional autothermal reformer (ATR) process contributes the largest exergy losses as a result of the large temperature driving force used in the syngas cooler. The novel ion transport membrane (ITM) oxygen technology has the potential to replace the cryogenic air separation and reduce the large power demands associated with oxygen production. Its high temperature operation makes it suitable for process integration with syngas production. Integration of this ITM oxygen technology into a natural gas to methanol flow sheet was investigated. The pinch analysis method was used to evaluate flow sheet minimum energy requirements and identify opportunities for process heat integration to reduce utility requirements. Exergy analysis was conducted to identify areas of large exergy destruction and opportunities for improvement and, to quantify and compare exergy losses of the flow sheet cases. Power cycles were integrated to efficiently recover and convert process heat to power. Performance of the power cycles was measured by the cycles’ thermal efficiencies. The overall plant and process efficiency as well as the specific iv gas efficiency were evaluated to assess and compare energy efficiency of the process flow sheet cases. Replacing the cryogenic ASU with ITM and integrating ITM oxygen into the ATR process is a more efficient method to recover the high temperature syngas heat with reduced exergy losses. The ITM oxygen unit integrated with power cycles resulted in 47% more power production compared to the conventional case A. The exergy analysis results showed a decrease in overall exergy losses by 26% in this new flow sheet. The ITM oxygen power cycle was found to produce enough power to drive its own compressors and with excess power of 28 MW, whereas the cryogenic ASU in the conventional case has a power demand of 33 MW. This work shows that lower cost production of oxygen may be the feasible solution to reduce the high costs of large-scale syngas manufacture. The ITM oxygen presents such opportunities by substituting the energy intensive cryogenic ASU and combining oxygen, syngas and power production into a single thermally integrated unit. The methanol loop was found to have sufficient process heat for combined heat and power production. The Rankine medium pressure (MP) steam cycle produced enough power to drive the syngas compressor. Configuring the methanol process into a power production cycle results in an increase in the flow sheet excess power production by 68% compared to the conventional case. However, reduced methanol production rate caused by lower flash pressures as well as reduced process heat for feed preheat are the main challenges to consider. The specific gas efficiency improved by 6% while carbon dioxide emissions decreased by 40%. The overall thermal efficiencies of the cases were not optimized as this was not part of the study objectives. A further study can be conducted to investigate improving the thermal efficiencies of the power cycles in each case by performing a sensitivity analysis to impact parameters such as turbine and compressor inlet temperature and v pressure ratio. The specific parameters to assess can be determined from the airstandard model equation for a Brayton power cycle. The thermal efficiency improvement can result in higher power production and reduced equipment duties which is a benefit to both capital and operating costs.
A dissertation submitted in partial fulfilment of the requirements for the degree Master of Science to the Faculty of Engineering and the Built Environment, School of Chemical and Metallurgical Engineering, University of the Witwatersrand, Johannesburg, 2023
Keywords: Natural gas; Methanol flow sheet